A Phenotypic-Driven Approach for the Diagnosis of WOREE Syndrome - Riva, Antonella; Nobile, Giulia; Giacomini, Thea; Ognibene, Marzia; Scala, Marcello; Balagura, Ganna; Madia, Francesca; Accogli, Andrea; Romano, Ferruccio; Tortora, Domenico; Severino, Mariasavina; Scudieri, Paolo; et al. (Frontiers in Pediatrics, 2022)
Background: WOREE syndrome is a rare neurodevelopmental disorder featuring drug-resistant epilepsy, global developmental delay, and ataxia. The disease, caused by biallelic pathogenic variants in the WWOX gene, usually leads to severe disability or death within the first years of life. Clinicians have become more confident with the phenotypic picture of WOREE syndrome, allowing earlier clinical diagnosis. We report a boy with a peculiar clinic-radiological pattern supporting the diagnosis of WOREE syndrome. Methods: DNA was extracted from blood samples of the proband and his parents and subjected to Exome Sequencing (ES). Agarose gel electrophoresis, real-time quantitative PCR (Q-PCR), and array-CGH 180K were also performed. Results: ES detected a pathogenic stop variant (c.790C>T, p.Arg264*) in one allele of WWOX in the proband and his unaffected mother. 180K array-CGH analysis revealed a 84,828-bp (g.chr16:78,360,803-78,445,630) deletion encompassing exon6. The Q-PCR product showed that the proband and his father harbored the same deleted fragment, fusing exons 5 and 7 of WWOX. Conclusions: Genetic testing remains crucial in establishing the definitive diagnosis of WOREE syndrome and allows prenatal interventions/parental counselling. However, our findings suggest that targeted Next Generation Sequencing-based testing may occasionally show technical pitfalls, prompting further genetic investigation in selected cases with high clinical suspicion.